EFEKTIVITAS PROGRAM KARANG TARUNA "MANGKUGURU" DALAM MENGURANGI PENGANGGURAN DI DESA MENGKURU KECAMATAN SAKRA BARAT KABUPATEN LOMBOK TIMUR - Muh. Zarkawi (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2020)
Mangkuguru youth community (karang taruna) was established on December 30, 2010 together with the inauguration of Mengkuru Village which was attended by the Regent of East Lombok in Mengkuru Village, West Sakra District, East Lombok Regency. This establishment was a manifestation of the spirit of caring of the younger generation to help prevent and address the problems of social socials welfare, especially those faced by children and adolescents in Mengkuru Village. This research was a descriptive qualitative research with the subject determination technique done by purposive sampling. The subject of the study was the Karang Taruna of Mengkuru. During the research, the processing of the data collected was the data of the Mangkuguru Youth Organization program which was obtained from documentation data and interviews. Data on the contribution of Karang Taruna Mengkuru obtained from observational data, documentation and interviews with several informants who were analyzed qualitatively. Based on the findings in the field, the Mangkuguru Youth Program was effective in reducing youth unemployment in the Mengkuru village, by creating a variety of programs in between, making bricks, making iron, farming, workshop and sending youth to work training. This shows that the contribution of young Mangkuguru youth organizations was quite effective and good for improving human resources in Mengkuru Village, West Sakra District, East Lombok Regency.